Richard the Lionheart : king and knight - Flori, Jean (Edinburgh University Press, 2006)
Richard I is the mythical king of England who preferred to wage war than to rule over his empire. This book examines Richard's role as prince and king in history in a chronological approach to his life, and analyzes the different and controversial elements which, for the chroniclers of his day, helped to make Richard a model of chivalry.